Perceived usefulness, perceived ease of use, perceived mutual relationship, perceived interactivity as determinants of social media use among pr practitioners - El-kasim, Mukhtar; Syed Arabi Idid, (Penerbit Universiti Kebangsaan Malaysia, 2016)
Social media diffusion has accentuated the practice of public relations across the globe. Studies established the social media’s impact in the promotion of mutual relationships between organizations and publics. However, most of these studies were focused on examining how organizations utilized social media as a whole, little attention was given on examining the perceptions of practitioners on social media as end users particularly from developing countries perspective. The aim of the current study was to investigate the perceptions of public relations practitioners on the relevance of social media for enhancing mutual relationship between organizations and their publics. This study utilized Technology Acceptance model (TAM) as theoretical framework. Specifically, practitioners’ perceptions on perceived usefulness, perceived ease of use, perceived mutual relationship, perceived interactivity and behavioral intention were examined. Five hundred and thirteen questionnaires were administered to public relations practitioners through a systematic random sampling. The data collected from the respondents were analyzed using Statistical Package for Social Sciences (SPSS). The results of t-test conducted on the five variable suggested that practitioners perceived social media as useful and easy to use in the promotion of mutual relationship between and organizations and their strategic publics. Hence, the result showed that practitioners have positive perceptions on the ability of social media to enhance mutual interactivity. Therefore, practitioners’ behavioral intention to use social media was influenced on the perceptions of the four other variables. However, the result of ANOVA revealed that, young practitioners have higher positive perception on perceived usefulness and perceived mutual relationships variables. The study provides recommendations and conclusion was drawn based on the findings of the study.